Simulation study of kenaf dust dispersion behavior in 20 L spherical chamber - Nurulain, Masrom; Nurud Suria, Suhaimi; Khairiah, Mohd Mokhtar; Juwari, Juwari; Noor Diana, Abdul Majid; Wan Zaiton, Wan Sulaiman (EDP Sciences, 2025)
To mitigate the risk of dust explosions, the study creates conditions such as those experienced in a silo to evaluate the dispersion properties of kenaf dust in a standard 20 L spherical chamber. In addition, factors such as particle tracks, particle velocities, static pressures, and turbulence kinetic energy (TKE) were also analyzed using the Computational Fluid Dynamics (CFD) simulations at dust concentrations of 250 g/m3, 500 g/m3, 750 g/m3, and 1000 g/m3. Based on the results, such concentration in terms of dust lowers the chances of explosions. The optimal parameters for turbulence and pressure reach at concentrations 1000 g/m3, which indicate a high possibility of kenaf dust explosion. The results suggest that there should be careful measures in housekeeping to control kenaf dust dispersion during industrial activities. The document presents recommendations for improving levels of regulatory compliance and safety in industries.